Deals and Delays : Firm-level Evidence on Corruption and Policy Implementation Times - Freund, Caroline; Hallward-Driemeier, Mary; Rijkers, Bob (Published by Oxford University Press on behalf of the World Bank, 2018)
Whether demands for bribes for particular government services are associated with expedited or delayed policy implementation underlies debates around the role of corruption in private sector development. The “grease the wheels” hypothesis, which contends that bribes act as speed money, implies three testable predictions. First, on average, bribe requests should be negatively correlated with wait times. Second, this relationship should vary across firms, with those with the highest opportunity cost of waiting being more likely to pay and facing shorter delays. Third, the role of grease should vary across countries, with benefits larger where regulatory burdens are greatest. The data are inconsistent with all three predictions. According to the preferred specifications, ceteris paribus, firms confronted with demands for bribes take approximately 1.5 times longer to get a construction permit, operating license, or electrical connection than firms that did not have to pay bribes and, respectively, 1.2 and 1.4 times longer to clear customs when exporting and importing. The results are robust to controlling for firm fixed effects and at odds with the notion that corruption enhances efficiency.